Pendampingan Perpajakan Bagi Pelaku UMKM Berbasis Syariah Melalui Edukasi Video Digital - Yunaita Rahmawati; Arik Dwijayanto (Jurnal Ilmiah Ekonomi Islam, 2022)
The Directorate General of Taxes routinely carries out various outreach activities like education and several government non-structural institutions that provide tax assistance for sharia-based Micro, Small, and Medium Enterprises (UMKM). This education and assistance are carried out by understanding the basic concepts of taxation, rights, and obligations for sharia-based UMKM owners. This education and assistance utilize the sophistication of information technology, one of which is through video and the use of applications. The purpose of this research is to find out how education and tax assistance through videos and applications can be carried out for sharia-based UMKM actors. This study used qualitative methods to facilitate data collection; observations and interviews were carried out. This study indicates that social media is the most appropriate method to convey information and has a strong persuasion power in today's society. In contrast, a video is a place for audio-visual learning that is easier to understand and understand as well as digital applications make it easier for the public to make payment systems and record taxes for sharia-based UMKM actors.